The emergence of everything : how the world became complex - Morowitz, Harold J. (Oxford University Press, 2002)
Framing the West argues that photography was intrinsic to British territorial expansion and settlement on the northwest coast. Williams shows how male and female settlers used photography to establish control over the territory and its indigenous inhabitants, as well as how native peoples eventually turned the technology to their own purposes. Photographs of the region were used to stimulate British immigration and entrepreneuralism, and imagies of babies and children were designed to advertise the population growth of the settlers. Although Indians were taken by Anglos to document their ""dis.